Reconciling Science and Faith: Galileo’s Theory of Biblical Interpretation - Yiwen, Sun (Theology and science, 2026)
Galileo’s exploration of the theory of biblical interpretation, which initially adhered to the Council of Trent's authority, proposed a groundbreaking integration of natural science into scriptural analysis. He believed that the precision of mathematics and the sensory-rational faculties given by God empower us to discern divine truths through scientific inquiry. This approach challenged the traditional medieval dichotomy between faith and science, offering a model to reconcile faith with empirical knowledge and expand our foundational understanding of God and the world.